2012
DOI: 10.1016/j.vaccine.2012.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Priming T-cell responses with recombinant measles vaccine vector in a heterologous prime-boost setting in non-human primates

Abstract: Highlights ► rMV vector immunization primes cellular responses to an adenovirus vector heterologous boost. ► rMV priming is highly effective for suboptimal doses of the boosting vector. ► Recombinant MV retains robust measles-specific humoral and cellular immunogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Further, both conventional and plasmacytoid human DCs were shown to cross-present tumor antigens and activate tumor-specific CTLs after exposure to measles virus-infected tumor cells [53,54]. Bolton et al previously showed that a measles vaccine vector can be used to prime SIV Gag-specific T cells in macaques, which could be amplified by a heterologous adenovirus boost [55]. Taken together, these data indicate that measles vaccines can be utilized for induction and promotion of antigen-specific CD8 + T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Further, both conventional and plasmacytoid human DCs were shown to cross-present tumor antigens and activate tumor-specific CTLs after exposure to measles virus-infected tumor cells [53,54]. Bolton et al previously showed that a measles vaccine vector can be used to prime SIV Gag-specific T cells in macaques, which could be amplified by a heterologous adenovirus boost [55]. Taken together, these data indicate that measles vaccines can be utilized for induction and promotion of antigen-specific CD8 + T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the aerosol route of administration is very effective in humans as a booster for the second MV immunization [38]. In a recent study that also used a vector based upon an attenuated measles virus strain, expressing SIV Gag, transgene immunity was found to be weak, but immunisation was carried out in pre-immune rhesus macaques, albeit in the absence of protective titres of measles neutralising antibodies [59]. That pre-existing immunity may have limited replication of attenuated vaccine virus resulting in low levels of transgene expression and immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The measles vector backbone was based on the Berna vaccine Edmonston Zagreb 19 strain (MVEZb; GenBank accession number HV542005.1), which constituted the measles component of the Triviraten Berna MMR vaccine (Schwarzer et al, 1998). The SIVgag transgene placed between the native P and M genes of rMVEZb2.SIVgag (Bolton et al, 2012) was digested with MluI and AatII and replaced by either the ORFs encoding the MuV-HN protein, the influenza virus HA protein or the RSV-F protein (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%